2005
DOI: 10.1152/japplphysiol.00160.2005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evidence for the role of physical activity in reducing risk of type 2 diabetes and cardiovascular disease

Abstract: Epidemiological studies suggest that physically active individuals have a 30-50% lower risk of developing type 2 diabetes than do sedentary persons and that physical activity confers a similar risk reduction for coronary heart disease. Risk reductions are observed with as little as 30 min of moderate-intensity activity per day. Protective mechanisms of physical activity include the regulation of body weight; the reduction of insulin resistance, hypertension, atherogenic dyslipidemia, and inflammation; and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
391
1
28

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(436 citation statements)
references
References 108 publications
(108 reference statements)
16
391
1
28
Order By: Relevance
“…However, a lack of physical activity has been shown to contribute to unhealthy blood glucose levels. 39,40 Additionally, though sitting time was controlled for, the HSE did not allow for assessment of duration of sitting episodes. Finally, this study is cross-sectional and therefore does not examine the study variables over time.…”
Section: Limitationsmentioning
confidence: 99%
“…However, a lack of physical activity has been shown to contribute to unhealthy blood glucose levels. 39,40 Additionally, though sitting time was controlled for, the HSE did not allow for assessment of duration of sitting episodes. Finally, this study is cross-sectional and therefore does not examine the study variables over time.…”
Section: Limitationsmentioning
confidence: 99%
“…The protective effect of physical activity becomes apparent even with moderateintensity exercise such as walking [3], and most studies report dose-response associations between physical activity and diabetes risk. The exact shape of this dose-response association remains uncertain though [4], and the difference in the reduction in risk between the least active and the next least active groups is not always significant [2]. There is a need to study this association further in diverse populations so as to improve the effectiveness of physical activity interventions to reduce diabetes in younger as well as in older populations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because the minimum amount of physical activity needed to achieve a decrease in the risk of developing type 2 diabetes is not well established [2,4,5], we tested whether even small amounts of weekly low-intensity physical activity reduce the risk of developing type 2 diabetes in comparison with physical inactivity. Moreover, we explored whether age modifies the association between categories of physical activity and incident type 2 diabetes because there is evidence that this association is stronger in older rather than in younger populations [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence has shown that levels of physical activity are also inversely and independently associated with TNFα , IL-6, and CRP (Panagiotakos et al 2005, Pischon et al 2003, Wannamethee et al 2002. As levels of physical activity have also consistently been shown to be inversely associated with the risk of developing both type 2 diabetes and cardiovascular disease (Bassuk & Manson 2005), markers of chronic low-grade inflammation could be a mediating link between levels of physical activity and chronic disease risk. However, the effect of walking, independent of more vigorous forms of exercise, on inflammatory markers is not well documented.…”
Section: Introductionmentioning
confidence: 99%